2021
DOI: 10.3389/fmicb.2021.677633
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence and Molecular Characteristics of New Delhi Metallo β-Lactamase-Producing Escherichia coli From Ducks in Guangdong, China

Abstract: This study aimed to determine the prevalence and transmission characteristics of New Delhi metallo β-lactamase (NDM)-producing Escherichia coli from ducks in Guangdong, China. In this study, a total of 28 NDM-producing E. coli isolates were recovered from 88 unduplicated diseased duck samples (31.8%) from veterinary clinics in Guangzhou, Foshan, Qingyuan, and Huizhou. Two variants, blaNDM−1 and blaNDM−5, were detected and the latter was present in 89.6% of the isolates (25/28). Multilocus sequence typing (MLST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Importantly, mcr-1 -bearing ST10 E. coli was found in pigs, pork, and humans simultaneously, which demonstrates that ST10 E. coli is an important vehicle for the spread of mcr-1 among animals, foods, and humans. Especially, ST10 E. coli was also the vehicle for other resistance genes such as the tigecycline resistance gene tet (X4) ( 24 ), the carbapenem resistance gene bla NDM-5 ( 25 ), the fosfomycin resistance gene fosA3 , and the extended-spectrum-β-lactamase (ESBL)-encoding genes bla OXA and bla TEM ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mcr-1 -bearing ST10 E. coli was found in pigs, pork, and humans simultaneously, which demonstrates that ST10 E. coli is an important vehicle for the spread of mcr-1 among animals, foods, and humans. Especially, ST10 E. coli was also the vehicle for other resistance genes such as the tigecycline resistance gene tet (X4) ( 24 ), the carbapenem resistance gene bla NDM-5 ( 25 ), the fosfomycin resistance gene fosA3 , and the extended-spectrum-β-lactamase (ESBL)-encoding genes bla OXA and bla TEM ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we downloaded all available complete genomes ( n =5 974; as of 1 September 2021) of Enterobacteriaceae submitted to the NCBI assembly database (https://www.ncbi.nlm.nih.gov/assembly/) and found only five bla NDM-5 -carrying IncHI2 plasmids (four from ducks and one from swine), all of which were from Guangdong, China. Although we could not trace the location of the grass carp farms and investigate the contamination source of the bla NDM-5 -positive Enterobacteriaceae , it is worth noting that the detection rate of the bla NDM gene in duck samples from Guangdong is high (>30%) ( Wang et al, 2021b ) and integrated duck-fish farming is very common in Guangdong ( Shen et al, 2020 ). In the duck-fish farm model, duck feces are discharged without treatment, and a large number of ARGs or residual agents can directly contaminate the fish ponds, promoting the transmission of ARGs between ducks and fish.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also reported some co-existence of resistant-genes in Enterobacteriaceae, like fosA3 and bla KPC−2 (Tang et al, 2020), or mcr-1 and bla NDM−5 (Sun et al, 2016), these co-existences make the strain become extensively drug-resistant to multiple antibiotics. Notably, although there are several reports about the co-existence of mcr-1 and bla NDM−5 in one plasmid or two separated plasmids, most of these plasmids were harbored by E. coli strains of animal origin or environmental origin, which is uncommon in K. pneumoniae (Yang et al, 2016;Quan et al, 2017;Mao et al, 2018;Wang et al, 2018Wang et al, , 2021Chen et al, 2019;Liu and Song, 2019;Han et al, 2020;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%